Analisis Kemampuan Membaca Intensif Siswa Kelas 3 Sekolah Dasar - Asiatul Fadilla; Chandra Chandra; Inggria Kharisma (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to analyze intensive reading skills among fifth-grade elementary school students. Intensive reading is a vital skill that supports information comprehension and serves as a foundation for mastering other subjects. The research employs a qualitative descriptive approach using a case study method. Data were collected through direct observation, audio recordings, and document analysis of previous reading assessment results. Evaluation involved cognitive tests with multiple-choice questions and psychomotor observations while students read texts independently. The findings reveal variations in intensive reading skills among students, particularly in understanding text content, organizing ideas, diction accuracy, sentence structure, spelling, and note-taking ability. Most students could grasp the main idea and identify the plot well; however, challenges remained in using appropriate diction, maintaining consistent sentence structure, and achieving accuracy in spelling and note-taking. These results highlight the need for more effective teaching strategies to improve students’ intensive reading skills. This study is expected to contribute positively to the development of Indonesian language learning methods at the elementary level, better preparing students to face increasingly complex academic challenges.